1986
DOI: 10.2170/jjphysiol.36.683
|View full text |Cite
|
Sign up to set email alerts
|

Responses of arcuate neurons to some putative neurotransmitters in perfused rat hypothalamic slices : Effects of in vivo and in vitro estrogen treatments.

Abstract: The responses of neurons in the arcuate nucleus (ARC) to yaminobutyric acid (GABA), glycine, serotonin (5-HT), norepinephrine (NE), and dopamine (DA) were examined in hypothalamic slices from ovariectomized rats either treated or untreated with estrogen. In estrogenuntreated preparations, spontaneous unit activity of the majority of neurons identified antidromically by the median eminence (ME) stimulation was depressed by GABA and glycine. When effective, 5-HT was predominantly excitatory and DA was predominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…We previously showed that 5-HT facilitated and inhibited spontaneous activity of 49 and 23%, respectively, of presumed TI neurons in the ARC (NIsHIHARA et al, 1986). It is possible that 5-HT directly inhibits the excitability of TI dopaminergic neurons which release dopamine as a PRL releaseinhibiting hormone.…”
mentioning
confidence: 96%
“…We previously showed that 5-HT facilitated and inhibited spontaneous activity of 49 and 23%, respectively, of presumed TI neurons in the ARC (NIsHIHARA et al, 1986). It is possible that 5-HT directly inhibits the excitability of TI dopaminergic neurons which release dopamine as a PRL releaseinhibiting hormone.…”
mentioning
confidence: 96%
“…In fact, implantation of GABA directly into the ARC has been reported to decrease the release of lu teinizing hormone [23]. Again, extracellular recordings have in dicated that GABA decreases the activity of most ARC neurons [24], GABA acts on at least two different receptors. Activation of the GABAa receptor increases a chloride conductance [for review see 25].…”
mentioning
confidence: 99%
“…Side-by-side bipolar electrodes, made of stainless steel wires (diameter: 100 pm) insulated except at the tip, were used for the stimulation. The sti mulating electrode was placed on the ME, and identification of neurons showing action potentials with antidromic features was made as reported previously (12], By the perfusion method, 3.7-10 nM l7|i-estradiol (E2 ; Sigma) or 3-5 pg/m l PRL (NIADDKrPRL-B-5, NIADDK-NIH) was applied to the slices. Changes in the firing rate greater than 30% or that in the preceding period were regarded as significant.…”
mentioning
confidence: 99%
“…The animals were sacri ficed by decapitation and sagittal medial-hypothalamic slices (300-400 pm in thickness), bordered anteriorly by the optic chiasm and posteriorly by the mammillary body, were prepared as pre viously described (12). Slices were preincubated for more than 30 min in the regular medium (concentrations in mM: NaCI 124; KC1 5; KH2 PO4 1.25; MgS04 1.3; NaHCOj 26; CaCI: 1.2, and glucose 10) saturated with an O2/C O 2 (95%/5%) gas mixture at 36 °C, and were then transferred to the recording chamber.…”
mentioning
confidence: 99%